2022
DOI: 10.1166/jbn.2022.3347
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Efficacy of a Tumor Nanovaccine and Artificial Antigen Presenting Cell-Based System as a Combination Therapy in a Mouse Model of Melanoma

Abstract: Tumor cell lysate (TCL)-based vaccines contain a large number of tumor-specific and related antigens, albeit at low levels, that require active transfer and presentation by antigen-presenting cells (APCs) in vivo, which stimulate a weak immune response. The artificial APC (aAPC) system presented herein is a cell-based therapeutic system that can significantly enhance the immune response compared to TCL-based vaccines. This study combines these two treatment strategies to assess their in vitro and in vivo effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Currently, the artificial APC (aAPC) technique stands as a cell-based therapeutic approach that can significantly enhance the immune response in comparison to TCL-based vaccinations [ 347 ]. NPs act as an effective carrier of antigen and promote the effective presentation of antigen to immune cells [ 348 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the artificial APC (aAPC) technique stands as a cell-based therapeutic approach that can significantly enhance the immune response in comparison to TCL-based vaccinations [ 347 ]. NPs act as an effective carrier of antigen and promote the effective presentation of antigen to immune cells [ 348 ].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation by Song revealed that the combination of TCL-poly (lactic-co-glycolic acid)-PEI (TPP) tumor nanovaccines and aAPCs induced a greater immune response and achieved better antitumor results than individual therapies. This combined therapy increased proliferation activities, inhibited regulatory T cells, promoted inflammatory cytokine production, and reduced inhibitory cytokine production [ 347 ]. Lipid NPs, due to their lipid bilayer structure, are well suited to simulate cell membranes and enhance antigen presentation and subsequent immune response [ 349 ].…”
Section: Introductionmentioning
confidence: 99%